An infection control protocol: effectiveness of immersion solutions to reduce the microbial growth on dental prostheses - Pavarina, Ana Claudia [UNESP]; Pizzolitto, A. C.; Machado, Ana Lucia [UNESP]; Vergani, Carlos Eduardo [UNESP]; Giampaolo, E. T. (Blackwell Publishing, 2003)
This investigation evaluated the effectiveness of an infection control protocol for cleansing and disinfecting removable dental prostheses. Sixty-four dentures were rubbed with sterile cotton swab immediately after they had been taken from patients' mouths. Samples were individually placed in the culture medium and immediately incubated at 37 +/- 2 degreesC. The dentures were scrubbed for 1 min with 4% chlorhexidine, rinsed for 1 min in sterile water and placed for 10 min in one of the following immersion solutions: 4% chlorhexidine gluconate, 1% sodium hypochlorite, Biocide (iodophors) and Amosan (alkaline peroxide). After the disinfection procedures, the dentures were immersed in sterile water for 3 min, reswabbed and the samples were incubated. All samples obtained in the initial culture were contaminated with micro-organisms. All the lower dentures immersed in Biocide showed positive growth, and the upper dentures were positive for growth in six of eight dentures. The 4% chlorhexidine gluconate, 1% sodium hypochlorite and Amosan solutions have been proved effective to reduce the growth of the micro-organisms in the 10 min immersion period. The protocol evaluated in this study seems to be a viable method to prevent cross-contamination between dental personnel and patients.
Keywords: removable prosthodontics; denture base acrylic resin; disinfection; cross-contamination